Acoustic metamaterials and phononic crystals - Boechler, N. (Springer series in solid-state sciences / editors, M. Cardona [y otro cinco], 2013)
This comprehensive book presents all aspects of acoustic metamaterials and phononic crystals. The emphasis is on acoustic wave propagation phenomena at interfaces such as refraction, especially unusual refractive properties and negative refraction. A thorough discussion of the mechanisms leading to such refractive phenomena includes local resonances in metamaterials and scattering in phononic crystals.